Holy Day or Holiday? The Giddy Trolley and the Canadian Sunday, 1890-1914 - Meen, Sharon (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1980)
The arrival of the electric street car in Canadian cities coincided with changing attitudes towards Sunday. The question of whether or not street cars might run on Sunday prompted a public debate concerning the proper use of the Sabbath — should it be a Holy Day or a holiday? This article examines the nature of the controversy over the Sunday street car and the struggle between the Sunday car and its Sabbatarian opponents. Sabbatarians challenged the Sunday car in a variety of ways but found it a most vexing and elusive target. By 1914, the Sunday car had triumphed, running merrily in cities from coast to coast. Its success, this article suggests, was due to support it received from the public, governments and the courts.